Pengaruh Perlakuan Temperatur pada Sintesis Bentonit Terpilar Al2O3 terhadap Karakternya dan Aplikasinya Sebagai Katalis dalam Reaksi Esterifikasi - Puji Wahyuningsih; Karna Wijaya; Wega Trisunaryanti (Fakultas Teknik Universitas Samudra, 2014)
The synthesis and characterization of Al2O3 pillared bentonite have been done and its application as catalyst for esterification reaction were studied. The effect of temperature treatment on the synthesis of Al2O3 pillared bentonite towards its characters were studied by calcinations methods with temperature variation 300, 400, and 500 oC for 4 h. The increasing of temperature on the synthesis of Al2O3 pillared bentonite was caused decreased of basal spacing, total pore volume and specific surface area bentonite. Characterizations were performed by using X-Ray Diffraction (XRD), N2 gas sorption analysis methods and FTIR analysis. The esterification reactions were conducted using acetic acid and ethanol. The ester products then were analyzed by Gas Chromatography (GC). Catalytic activity test showed that the percentage of ethyl acetate produced by Al2O3-pillared natural bentonite and natural bentonite catalyzed reactions were 16,74 and 8,61 %, respectively, eventhough natural bentonite surface acidity was higher than Al2O3-pillared natural bentonite. It was demonstrated also that catalytic activity was not influenced merely by surface acidity but also influenced by specific surface area and total pore volume.